IL-17 Induced Autophagy Regulates Mitochondrial Dysfunction and Fibrosis in Severe Asthmatic Bronchial Fibroblasts - Ramakrishnan, Rakhee K.; Bajbouj, Khuloud; Al Heialy, Saba; Mahboub, Bassam; Ansari, Abdul Wahid; Hachim, Ibrahim Y.; Rawat, Surendra; Salameh, Laila; Hachim, Mahmood Y.; Olivenstein, Ronald; Halwani, Rabih; Hamoudi, Rifat; et al. (Frontiers in Immunology, 2020)
The accumulation of fibroblasts, their synthesis of extracellular matrix (ECM) proteins and their innate resistance to apoptosis are characteristics of subepithelial fibrosis observed in severe asthma. Interleukin-17 (IL-17) is an important regulator of airway remodeling in asthma. However, the contribution of IL-17 to the pro-fibrotic phenotype of bronchial fibroblasts is not well-characterized. In this study, we investigated whether IL-17 induced autophagy regulates mitochondrial and pro-fibrotic function in bronchial fibroblasts. The primary cultured bronchial fibroblasts isolated from non-asthmatic (NHBF) and severe asthmatic (DHBF) subjects were treated with IL-17 in order to ascertain its effect on mitochondrial function, mitochondrial quality control, and apoptosis using immunoblotting and flow cytometric analyses. At baseline, DHBF exhibited higher levels of mitophagy and mitochondrial biogenesis compared to NHBF. Immunohistochemical evaluation of bronchial biopsies showed intense PINK1 immunoreactivity in severe asthma than in control. IL-17 intensified the mitochondrial dysfunction and impaired the mitochondrial quality control machinery in NHBF and DHBF. Moreover, IL-17 augmented a pro-fibrotic and anti-apoptotic response in both group of fibroblasts. Inhibition of autophagy using bafilomycin-A1 reduced PINK1 expression in NHBF and restored the IL-17 mediated changes in PINK1 to their basal levels in DHBF. Bafilomycin-A1 also reversed the IL-17 associated fibrotic response in these fibroblasts, suggesting a role for IL-17 induced autophagy in the induction of fibrosis in bronchial fibroblasts. Taken together, our findings suggest that IL-17 induced autophagy promotes mitochondrial dysfunction and fibrosis in bronchial fibroblasts from both non-asthmatic and severe asthmatic subjects. Our study provides insights into the therapeutic potential of targeting autophagy in ameliorating fibrosis, particularly in severe asthmatic individuals.